Dramatically enhanced thermal properties for TiO2-based nanofluids for being used as heat transfer fluids in concentrating solar power plants. (April 2018) - Yasinskiy, Andrey; Navas, Javier; Aguilar, Teresa; Alcántara, Rodrigo; Gallardo, Juan Jesús; Sánchez-Coronilla, Antonio; Martín, Elisa I.; De Los Santos, Desireé; Fernández-Lorenzo, Concha
Abstract: The paper presents an analysis of the properties of TiO2 -based nanofluids such as their physical stability and heat transfer performance. The nanofluids were prepared with a eutectic mixture of diphenyl oxide and biphenyl with the addition of TiO2 nanoparticles and 1-octadecanethiol (ODT), used as a surfactant. The nanofluids were tested to determine their thermal and physical properties, such as stability, density, viscosity. The introduction of TiO2 nanoparticles accompanied with equal quantity of ODT was seen to sharply enhance the properties of the system in terms of heat transfer in concentrating solar power (CSP) plants. In particular, the system became stable after 3–5 days, and the settlement rate depended on the nanoparticle concentration. There was a slight increase in density and viscosity of no more than 0.12% and 4.85%, respectively. The thermal properties improved significantly, up to 52.7% for the isobaric specific heat and up to 25.8% for the thermal conductivity. The dimensionless Figure of Merit parameter (FoM), which is based on the Dittus-Boelter correlation, was used as a criterion for evaluating efficiency. At all the temperatures tested the nanofluid with 2.5·10 −4 wt% (volume fraction of 2.44%) of TiO2 performed best, increasing the efficiency by up to 35.4% with regard to the pure heat transfer fluid (HTF) used in CSP plants. Thus, nanofluids based on TiO2 nanoparticles seem to be a promising alternative to HTFs in CSP plants. Highlights: This manuscript reports TiO2-based nanofluids for being used in CSP plants. The thermal properties were dramatically enhanced with respect to the base fluid. The isobaric specific heat improved significantly up to 25.8%. The thermal conductivity increased up to 52.7%. The efficiency of these nanofluids was improved up to 35%.